The critic’s voice: On the role and function of criticism of classical music recordings - Alessandri, Elena; Baldassarre, Antonio; Williamson, Victoria Jane (Frontiers in Psychology, 2022)
In the Western classical tradition music criticism represents one of the most complex and influential forms of performance assessment and evaluation. However, in the age of peer opinion sharing and quick communication channels it is not clear what place music critics’ judgements still holds in the classical music market. This article presents expert music critics’ view on their role, function, and influence. It is based on semi-structured interviews with fourteen native English- and German-speaking critics who had an average of 32 years professional activity in classical music review. We present the first visual model to summarise music critics’ descriptions of their role and responsibilities, writing processes, and their influences (on the market and on artists). The model distinguishes six roles (hats): consumer adviser, teacher, judge, writer, stakeholder, and artist advocate. It identifies core principles governing critical writing for music as well as challenges that arise from balancing the above six responsibilities whilst remaining true to an implicit code of conduct. Finally, it highlights the factors that inform critics’ writing in terms of the topics they discuss and the discursive tools they employ. We show that music critics self-identify as highly skilled mediators between artists, producers and consumers, and justify their roles as judge and teacher based on a wealth of experience as against the influx of pervasive amateur reviews. Our research approach also offers occupation-based insights into professional music review standards, including the challenges of maintaining objectivity and resisting commercial pressures. This article offers a new viewpoint on music critics’ judgements and recommendations that helps to explain their expectations and reflections.